Adult literacy fundamentals mathematics. Book 3 - Tagami, Wendy; Girard, Liz; BC Open Textbook Project; BCcampus; British Columbia Ministry of Advanced Education and Labour Market Development (Ministry of Advanced Education and Labour Market Development, 2010)
"Fundamental mathematics for adult learners. Book 3 includes a Table of Contents, Glossary, Grades Records, Self Tests, Practice Tests and Unit Tests. Ancillary Resources include the Instructor's Manual. This is 1 of a series of 6 books in the ABE Math collection."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from website description.
Keywords: Mathematics -- Textbooks; Electronic books